1991
DOI: 10.2166/wst.1991.0588
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Properties and Simultaneous Nitrification and Denitrification in Aerobic Rotating Biological Contactors

Abstract: The properties of a blofllm developed on a Rotating Biological Contactor (RBC), such as the spaclal distribution of blofllm density, bacterial population and Intrinsic biochemical reaction rates, were measured. The blofllm density and the number of heterotrophs, nltrlflers and denltrlflers per unit volume of blofllm Increased with the blofllm depth. However, the intrinsic reaction rates per unit blomass did not significantly change with depth. Based on the above evidence, experiments on simultaneous nitrificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…The obtained cell densities were in agreement with the results of Masuda et al 17 and Zhang et al 34 However, the experimental results were quite different from the model predictions. The major difference is that the models predicted more pronounced stratifications of nitrifiers and heterotrophs than the observed results.…”
Section: Spatial Microbial Distributionsupporting
confidence: 89%
See 1 more Smart Citation
“…The obtained cell densities were in agreement with the results of Masuda et al 17 and Zhang et al 34 However, the experimental results were quite different from the model predictions. The major difference is that the models predicted more pronounced stratifications of nitrifiers and heterotrophs than the observed results.…”
Section: Spatial Microbial Distributionsupporting
confidence: 89%
“…Since the binary population biofilms were used, the experimentally observed spatial distribution of two species agreed well with the model predictions. Masuda et al 17 and Zhang et al 34 have measured microbial spatial distributions of nitrifiers in mixed-population biofilms using the microslicing technique. Although they have found the stratified spatial distribution of nitrifiers, they have not discussed interspecies competition or verified the biofilm models.…”
Section: Introductionmentioning
confidence: 99%
“…Some simultaneous nitrification and denitrification phenomena were reported [2]. The phenomena can be explained by the diffusional limitation of oxygen into the microbial floc and biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that, the rate of substrate consumption increased as the bio®lm thickness increased upto a limiting depth of 70±100 lm, and after that removal rate was independent of depth. Ishiguro 1978, andMasuda et al (1991), have studied the bio®lm properties in a rotating biological contactor (RBC) plant, treating the leachate from a sanitary land®ll to discover the factors in¯uencing the simultaneous nitri®cation and denitri®cation. They de®ned the bio®lm thickness as the maximum height of a bio®lm segment.…”
Section: Measurement Of Film Thicknessmentioning
confidence: 99%